2005
DOI: 10.1016/j.ajo.2005.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve diffusion measurement from diffusion-weighted imaging in optic neuritis

Abstract: BACKGROUND AND PURPOSE:Increases in apparent diffusion coefficient (ADC) from diffusion-weighted (DW) imaging are thought to be due to axonal disruption, and changes have been well documented in multiple sclerosis lesions. DW imaging of the optic nerves, however, presents many challenges. The goal of this study was to measure ADC in patients with optic neuritis by using zonal oblique multisection echoplanar imaging.METHODS: The optic nerves of eighteen patients who had experienced an attack of optic neuritis 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 27 publications
5
78
1
Order By: Relevance
“…15,16 DWI has been a complementary technique useful in the differential diagnosis of orbital pathologies such as orbital inflammatory syndrome, orbital lymphoid lesion, orbital cellulitis, acute optic nerve infarction, endophthalmitis, acute ischemic homonymous hemianopsia, indeterminate orbital masses, and optic neuritis. [18][19][20][21][22][23] Also, Politi et al 24 recorded the ADC of the vitreous humor in healthy subjects as part of a normative data collection for a larger study of orbital masses and found a mean vitreal ADC that is significantly lower than that in our results; the difference might be due to different techniques used in the studies.…”
Section: Discussioncontrasting
confidence: 54%
“…15,16 DWI has been a complementary technique useful in the differential diagnosis of orbital pathologies such as orbital inflammatory syndrome, orbital lymphoid lesion, orbital cellulitis, acute optic nerve infarction, endophthalmitis, acute ischemic homonymous hemianopsia, indeterminate orbital masses, and optic neuritis. [18][19][20][21][22][23] Also, Politi et al 24 recorded the ADC of the vitreous humor in healthy subjects as part of a normative data collection for a larger study of orbital masses and found a mean vitreal ADC that is significantly lower than that in our results; the difference might be due to different techniques used in the studies.…”
Section: Discussioncontrasting
confidence: 54%
“…In the past, these changes were monitored by imaging techniques. 20,21,22 Optic neuritis is a disease of younger population, and majority of our patients too were in the age group of 10-19 years. In a study by Morales et al, children had bilateral disease more often than in adults, prognosis for visual function recovery was poorer, and nearly 26% went on to develop MS. 23 Most of the ophthalmologists and neurologists would treat patients with ON with intravenous methylprednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…However, optic nerve DTI is extremely challenging, and higher field strengths pose further problems despite the potentially increased SNR and resolution. Several approaches have been published, but many require unconventional pulse sequence design and hence sequence development (Dowell et al, 2009;Hickman et al, 2005;Koch et al, 2002;Naismith et al, 2009;Trip et al, 2006;Wheeler-Kingshott et al, 2002;Xu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the pixel resolution could be reduced (although in the case of the optic nerve this is not a desirable option as, due to its small size, high resolution is required to avoid major partial volume issues), or multi-shot EPI could be used (although navigator echoes would then be required for motion correction between shots). For small objects such as the optic nerve, the echo train length could be reduced by reducing the FOV, however this may result in aliasing (wraparound artifact), unless techniques such as ZOOM-EPI [e.g., (Hickman et al, 2005)] are employed. These techniques, however, are not available on all clinical scanners, including the one used in this study, and therefore a research agreement with the manufacturer and sequence programming efforts would be needed.…”
Section: Introductionmentioning
confidence: 99%